Volume 9: Mechanical Systems and Control, Parts A, B, and C 2007
DOI: 10.1115/imece2007-42724
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Time Delay of the Semi-Active Dampers on the Performance of On-Off Control Schemes

Abstract: With the new advancement in the vibration control strategies and controllable actuator manufacturing, the semi-active actuators (dampers) are finding their way as an essential part of vibration isolators, particularly in vehicle suspension systems. The currently available semi-active damper technologies can be divided into two main groups. The first uses controllable electromagnetic valves. The second uses magnetorheological (MR) fluid to control the damping characteristics of the system. Despite different sem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 0 publications
0
5
0
Order By: Relevance
“…The use of current controller instead of the voltage controller can significantly reduce the overall response time [6]. Although many studies simulating suspension systems with MR dampers controlled by semi-active algorithms do not take into consideration the response time of MR dampers [7][8][9], papers [10][11][12] showed the considerable influence of the MR damper response time on suspension efficiency. The simulations and measurements showed that for a passenger car with a typical unsprung mass natural frequency of 18 Hz, the primary response time (0%-63%) must be much shorter than 8 ms.…”
Section: Introductionmentioning
confidence: 99%
“…The use of current controller instead of the voltage controller can significantly reduce the overall response time [6]. Although many studies simulating suspension systems with MR dampers controlled by semi-active algorithms do not take into consideration the response time of MR dampers [7][8][9], papers [10][11][12] showed the considerable influence of the MR damper response time on suspension efficiency. The simulations and measurements showed that for a passenger car with a typical unsprung mass natural frequency of 18 Hz, the primary response time (0%-63%) must be much shorter than 8 ms.…”
Section: Introductionmentioning
confidence: 99%
“…While studying and performing numerical and experimental studies on the issue of response time of semi-active dampers [15], it was clear that if the response time of a semi-active damper increases, the added nonlinearity effect diminishes. This observation initiates the idea of this modified controller.…”
Section: A Modified Controller To Eliminate the Added Nonlinearities mentioning
confidence: 99%
“…As depicted, the proposed system eliminates the added nonlinearities effectively. It is important to mention that this process will deteriorate the performance of the semi-active control systems [15] to some extent and, as a result, each case should be studied individually and the proper filtering parameter (a) determined. This process is also dependent on the response time of the actual semi-active actuator used in the system.…”
Section: A Modified Controller To Eliminate the Added Nonlinearities mentioning
confidence: 99%
“…Huang et al thought that the integral time constant brings time delay into the semiactive control system, and the value is about 30 ms [25]. Eslaminasab and Golnaraghi measured that response time delay of the MR damper is about 10 ms, but response time delay of the solenoid-type damper is about in the range of 12.5∼16.5 ms [26,27]. Cha et al believed that a MR damper of 200 kN capacity needs 18 ms to reach the required control current and 550 ms to reach the required damping force [28].…”
Section: 3mentioning
confidence: 99%